Molecular Imaging of Pancreatic Cancer with Antibodies - England, Christopher G. (Mol Pharm, 2015)
[Image: see text] Development of novel imaging probes for cancer diagnostics remains critical for early detection of disease, yet most imaging agents are hindered by suboptimal tumor accumulation. To overcome these limitations, researchers have adapted antibodies for imaging purposes. As cancerous malignancies express atypical patterns of cell surface proteins in comparison to noncancerous tissues, novel antibody-based imaging agents can be constructed to target individual cancer cells or surrounding vasculature. Using molecular imaging techniques, these agents may be utilized for detection of malignancies and monitoring of therapeutic response. Currently, there are several imaging modalities commonly employed for molecular imaging. These imaging modalities include positron emission tomography (PET), single-photon emission computed tomography (SPECT), magnetic resonance (MR) imaging, optical imaging (fluorescence and bioluminescence), and photoacoustic (PA) imaging. While antibody-based imaging agents may be employed for a broad range of diseases, this review focuses on the molecular imaging of pancreatic cancer, as there are limited resources for imaging and treatment of pancreatic malignancies. Additionally, pancreatic cancer remains the most lethal cancer with an overall 5-year survival rate of approximately 7%, despite significant advances in the imaging and treatment of many other cancers. In this review, we discuss recent advances in molecular imaging of pancreatic cancer using antibody-based imaging agents. This task is accomplished by summarizing the current progress in each type of molecular imaging modality described above. Also, several considerations for designing and synthesizing novel antibody-based imaging agents are discussed. Lastly, the future directions of antibody-based imaging agents are discussed, emphasizing the potential applications for personalized medicine.